Pengaruh Biaya Tambat dan Biaya Handling Terhadap Efektivitas Bongkar Muat Curah Kering di PT. Berlian Manyar Sejahtera - Muhamad Rizky Rachman Hakim; Indah Ayu Johanda Putri; Teguh Pribadi; Faris Nofandi (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study aims to determine the effect of mooring costs and handling costs on the effectiveness of dry bulk loading and unloading. In supporting activities at the Port, the process of loading and unloading dry bulk often has cost factors that can affect the effectiveness of completion time. The method used is quantitative, which is analysed with SPSS version 27 with several components, such as assumption tests, classical, correlation coefficient, multiple linear regression, and hypothesis testing. The results of this study indicate that mooring fees have a significant and positive effect on the effectiveness of loading and unloading, where an increase in mooring fees encourages the acceleration of the loading and unloading process. handling costs partially do not show a significant effect on effectiveness, but simultaneously with mooring fees have a significant effect. This research provides insight for PT Berlian Manyar Sejahtera in optimising operational cost management to improve the efficiency and effectiveness of loading and unloading activities